Higher adalimumab maintenance regimen is more effective than standard dose in anti-TNF experienced Crohn's disease patients. Issue 10 (16th August 2021) - Greener, Tomer; Boland, Karen; Milgrom, Raquel; Ben-Bassat, Ofer; Steinhart, A. Hillary; Silverberg, Mark. S.; Narula, Neeraj
Abstract : Background: Many Crohn's disease patients treated with anti-tumor necrosis factor (TNF) therapies suffer from loss of response over time and require dose escalation. The aim of this study was to evaluate the efficacy and safety of treating anti-TNF experienced Crohn's disease patients with higher maintenance regimens of adalimumab. Methods: In a retrospective observational study, Crohn's disease patients receiving adalimumab were categorized according to their maintenance regimen; 40 mg weekly, 80 mg every other week or greater were defined as a high-dose maintenance regimen and 40 mg every other week was defined as a standard maintenance regimen. The primary outcome was time to treatment failure. Results: Thirty-nine patients were started on high-dose regimens following induction and 40 patients received the standard regimen. According to a Kaplan–Meier survival curve analysis, time to treatment failure was significantly longer in patients in the high-dose group ( P  = 0.0015). Patients on high-dose adalimumab had a lower treatment failure rate (hazard ratio 0.21; P  = 0.0005) when compared to patients on the standard regimen, after adjusting for induction dose and concomitant immunomodulator use. No difference in adverse events was identified between the groups (31 vs. 30%; P  = 0.94). Conclusion: High-dose maintenance regimens were more effective than the standard adalimumab maintenance protocol with better short and long-term clinical outcomes.